Canal control alternatives in the irrigation district Sector-BXII del Bajo Guadalquivir, Spain - Lozano, David (2012)
Improved water management and efficient investment on the modernization of the irrigation districts in most countries are imperative to satisfy the increasing demand of water. The automation and control of their main canals is one mean to increase the efficiency and flexibility of the irrigation systems. In 2005, we monitored one canal in the irrigation district ‘Sector BXII del Bajo Guadalquivir’. This is a representative irrigation canal of the irrigation districts in Southern Spain. This canal is divided into four pools and supplies an area of 5,150 ha. We used ultrasonic sensors and pressure transducers to record water levels upstream and downstream each canal pool. With the measured data and the hydraulic model SIC (Simulation of Irrigation Canals), we evaluated two canal control alternatives (local upstream control and distant downstream control) using a Proportional-Integral (PI) control algorithm. First, we calibrated and validated SIC under steady-state conditions. Then, we calibrated the proportional and integral gains of the PI algorithm. The obtained results show that only the distant downstream controller can quickly and automatically adjust the canal dynamics to unexpected water demands, with efficiency and no spills at the canal tail, even for sudden and significant flow variations.